Relationship between transformtion and institutional culture - Luvalo, L.M. (South African Journal of Higher Education, 2019)
Transformation of higher education (HE) is presently a buzzword in the higher education globally and in South Africa. Government policy has suggested a system of higher education relevant to the new South Africa. Since 1994 elections not enough transformation took place in South Africa. This was affirmed by violent student protests two years ago at universities sparked by fees’ hikes. In South Africa, institutional transformation and institutional culture have been approached as different phenomena, and recently it was demonstrated that the one cannot exist without the other. The turmoil at South African HE institutions in 2015 and early 2016 highlighted the issues of institutional transformation and institutional culture. The student protests were linked to lack of transformation and an institutional culture that alienates black students. This article explores the concepts of transformation and institutional culture, in the context of HE institutions. I conclude that these concepts are intertwined, therefore we cannot have a completely transformed HE in South Africa until the institutional culture also changes.